The Effect of Stiffening of Fully Composite Modular Footbridge on Horizontal Loads - Vašátko, David; Girgle, František; Kostiha, Vojtěch; Štěpánek, Petr (Vysoké učení technické v Brně,Fakulta stavební, 2024)
In the design of the footbridge structure, horizontal loads, primarily from wind effects, cannot be overlooked. During the research of the fully composite modular footbridge, low horizontal stiffness was revealed, which was significantly affected by the connection points. Horizontal stiffness is mainly controlled by the joint plates at the module connections, and therefore, horizontal stiffening in the plane of the cross members was proposed. The stiffening adheres to the modular system and does not interfere with the assembly of the footbridge for the required span. The different stiffness of the footbridge in the horizontal plane without and with the use of horizontal bracing was experimentally verified.
Keywords: Fully composite modular footbridge; horizontal loads test; effect of stiffening